2021
DOI: 10.1159/000511384
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-Weighted Imaging Reflects Tumor Grading and Microvascular Invasion in Hepatocellular Carcinoma

Abstract: <b><i>Background:</i></b> To date, there are inconsistent data about relationships between diffusion-weighted imaging (DWI) and tumor grading/microvascular invasion (MVI) in hepatocellular carcinoma (HCC). Our purpose was to systematize the reported results regarding the role of DWI in prediction of tumor grading/MVI in HCC. <b><i>Method:</i></b> MEDLINE library, Scopus, and Embase data bases were screened up to December 2019. Overall, 29 studies with 2,715 tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 52 publications
1
36
1
Order By: Relevance
“…However, with increasing recognition of MVI and its prognostic value on surgical outcomes of HCC, preoperative MVI prediction systems for surgical decision making have become a hot topic in recent researches. In recent years, some studies have reported the possibility of imaging findings to predict the MVI of HCC (24)(25)(26)(27). However, it still has a limited capacity to detect MVI and the precise detection of MVI needs further histological identification (28).…”
Section: Introductionmentioning
confidence: 99%
“…However, with increasing recognition of MVI and its prognostic value on surgical outcomes of HCC, preoperative MVI prediction systems for surgical decision making have become a hot topic in recent researches. In recent years, some studies have reported the possibility of imaging findings to predict the MVI of HCC (24)(25)(26)(27). However, it still has a limited capacity to detect MVI and the precise detection of MVI needs further histological identification (28).…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, this is the first systematic review aiming at summarizing the role of non-Gaussian diffusion MRI models in HCC. To date, systematic studies were performed on conventional diffusion metrics for HCC detection and prognosis [15,90,91]. Surov et al performed a meta-analysis to assess the role of DWI in prediction of tumor grading and MVI in HCC, also including D in the investigated metrics [15].…”
Section: Discussionmentioning
confidence: 99%
“…To date, systematic studies were performed on conventional diffusion metrics for HCC detection and prognosis [15,90,91]. Surov et al performed a meta-analysis to assess the role of DWI in prediction of tumor grading and MVI in HCC, also including D in the investigated metrics [15]. Wu et al performed a metaanalysis evaluating the IVIM model in differentiating focal liver lesions, also including HCC [78].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Attention was paid to excluding structures close to the rim of the lesion to avoid partial volume effects. These ROIs were transferred to the same slice of the ADCmap to calculate intralesional ADC values including minimal (ADCmin) and mean (ADCmean) ADC (below noted as 10 −3 mm 2 /s), as these reflect the most commonly assessed ADC values in current literature [23]. In addition, ADC mean values of tumor-free liver were assessed by drawing circular ROIs, as large as possible.…”
Section: Image Analysismentioning
confidence: 99%